Self-Organizing Network technique for resource allocation and mobility management in LTE femtocell network / Labeeb Mohsin Abdullah - Abdullah, Labeeb Mohsin (Institute of Graduate Studies, UiTM, 2016)
Ubiquitous mobile communication requires increased capacity and appropriate quality of services for real time applications. To meet these demands, the 4th generation LTE mobile network operators has deployed femtocell access points next to the conventional base station structure. This deployment will extensively enhance capacity and service coverage for the customers. However, the presence of femtocell generates new challenges. In this thesis, the issues of concern include assigning the limited resources of Physical Cell Identity (PCI) for the high number of deployed femtocells, to ensure network collision and confusion free after deploying the PCI, determine the exact geographic location of femtocell, and identifying the learning parameters for the optimized self-organizing handover process for LTE femtocell-based networks. The commonality between the aforementioned issues of concern is the adoption of Self- Organizing Network (SON) technology concept as the basis for the proposed solutions for the above-mentioned challenges. MATLAB and Vienna LTE simulators were used to conduct the experiments for the proposed algorithms, approaches and schemes and also used to verify the results…